Strength Analysis and Assessment of Ina-TEWS Wave Glider - Priohutomo, Kusnindar; Nugroho, Wibowo Harso; Yulfani, Rosi Dwi (International Journal of Natural Science and Engineering, 2020)
Indonesia as a country that often experiences tsunami disasters needs to have an early warning system against tsunami disasters. This system can use various existing technologies, one of which is the tsunami buoy system. The new tsunami buoy system does not use the natural mooring system but uses the wave glider system. This paper discusses the structural strength of the surface floater of wave glider using Eva Foam and Fiberglass material for skin and Alluminium material for frame and kell. The surface floater using 16 pieces for frame and 1 piece for keel. Enviromental loads is use in this paper like hydrodynamics load and weight load. The results from this paper is material from Eva Foam has a maximum principle stress is 12693 Pa and shear stress is 6114.6 Pa. For material from Fiberglass has maximum principle stress is 11.875 Pa and shear stress is 6076.3 Pa. Safety factor (SF) from maximum principle stress and shear stress for Eva Foams is up to 6x and SF for maximum principle and shear stress for Fiberglass is up to 26x. Conclusions for this paper is the desain for surface floater of wave glider it can be operated in the sea with draugh 0.18 m.